Primary omental hydatid cyst - Alis, Halil (Dove Medical Press, 2009)
Hydatid disease is still a frequently seen disease in endemic area like South America, Middle Asia and South Europe as well as Turkey. Although the disease occurs more frequently in liver and lungs, it can be seen in any part of the body. In this report we present a case of isolated omental hydatid disease which is a rare entity in the English literature.